The role of the student counselor in reducing school violence (From the point of view of student counselors on middle school schools in the city of Riyadh) - Al-Otaibi, Mohammed Marzouq Nawar (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the forms of violence practiced in the school from the point of view of the student counselors and to know the most important roles played by the student advisor to reduce school violence from the point of view of the student counselors, as well as to know the most prominent obstacles and difficulties that prevent the student advisor from playing his role in reducing violence The school counselors' point of view, in addition to identifying the means and methods that the student counselor can take to reduce school violence from the student counselors' point of view. The study was applied to a sample of (71) student counselors in the education offices in eastern Riyadh, and the researcher used the questionnaire as a tool for collecting the necessary data for the study. The most important roles played by the student advisor are to support religious and moral values, and to communicate with the guardian about his son's behavior. It was also found that the most important means and methods that the student counselor can take to reduce school violence are to encourage the student's positive achievements, as well as to create a positive relationship between the student and the school administration, and then not tolerate the student who commits violence.
Keywords: violence; school violence; counselor